New directions in information behaviour - Spink, Amanda; Heinström, Jannica, 1970- (Emerald, 2011)
New Research in Information Behavior, co-edited by Professor Amanda Spink and Dr. Jannica Heinström provides an understanding of the new directions, leading edge theories and models in information behavior. Information behavior is conceptualized as complex human information related processes that are embedded within an individuals everyday social and life processes. The book presents chapters by a range of scholars who show new research directions that often challenge the established views and paradigms of information behavior studies. Beginning with an evolutionary framework, the book builds our understanding of information behaviors over various epochs of human existence from the Palaeolithic Era and within pre-literate societies, to contemporary behaviors by 21st century humans. Drawing upon social and psychological science theories the book presents a more integrated and holistic approach understanding of information behaviours. This book is directly relevant to information scientists, information professionals and librarians, social and evolutionary psychologists, social scientists and people interested in understanding more about their own information behaviors.
Includes index.
Keywords: Information behavior.; elektronické knihy; electronic books